Costs of Flying Units in Air Force Active and Reserve Components - Robbert, Albert A. (RAND Corporation, 2013)
This report describes a methodology for compiling and comparing the costs of Air Force active- and reserve-component flying units. Using data from the Air Force Total Ownership Cost system, the author estimates the cost of operating the Air Force's active and reserve C-130, KC-135, and F-16 fleets; highlights how cost considerations favor the active and reserve components differently; and discusses how this can inform force mix decisions.